2002
DOI: 10.1097/01.lab.0000038503.34655.98
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of β-Galactoside α2,6 Sialyltransferase and Sialoglycans in Normal and Cirrhotic Liver and Hepatocellular Carcinoma

Abstract: SUMMARY:Sialyltransferases sialylate plasma glycoproteins in hepatocytes and may (as hepatic key enzymes) constitute markers for liver diseases. We examined expression of the prevalent ␣2,6 sialyltransferase (ST6Gal I) and sialoglycans in normal liver, cirrhotic liver, and hepatocellular carcinoma (HCC) using a new ST6Gal I-specific mAb and recombinant fusion proteins of CD22 and sialoadhesin recognizing ␣2,6-or ␣2,3-sialylated glycans in immunohistology and flow cytometry. In normal and cirrhotic liver, ST6Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…not been successful in differentiating HCC from benign liver tissue. [15][16][17][18][19] In the present study, we found that the pattern of immunostaining for AMACR distinguished benign nondysplastic hepatocytes from dysplastic or malignant hepatocytes. Dysplastic and malignant hepatocytes demonstrated a coarsely granular staining pattern with either a basal or diffuse distribution.…”
Section: Discussionmentioning
confidence: 95%
“…not been successful in differentiating HCC from benign liver tissue. [15][16][17][18][19] In the present study, we found that the pattern of immunostaining for AMACR distinguished benign nondysplastic hepatocytes from dysplastic or malignant hepatocytes. Dysplastic and malignant hepatocytes demonstrated a coarsely granular staining pattern with either a basal or diffuse distribution.…”
Section: Discussionmentioning
confidence: 95%
“…Some evidence can also be found that the expression of ST6GalI is up-regulated in human HCC patients and in a transgenic mouse model of HCC [47][48][49]. We already mentioned this enzyme in ALD where it was down-regulated.…”
Section: Alteration Of Glycosylation In Hepatocellular Carcinomamentioning
confidence: 91%
“…Briefly, the cells grown on coverslips were fixed in −20°C acetone for 10 minutes and then incubated with the rabbit anti-ERGIC3 polyclonal antibody (Abcam), and anti-MUC1 mouse monoclonal antibody (mAb) A76-A/C7 (Glycotope, Berlin, Germany), anti-ST mAb [15], anti-calreticulin mAb (Abcam), and anti-58K Golgi protein mAb (Abcam) at 4°C overnight. Following the washes, the cells were incubated with FITC-coupled anti-rabbit antibody (BD sciences, Franklin Lakes, NJ, USA) or with Cy3-coupled anti-mouse antibody (Millipore, Billerica, MA, USA) for 1 hour.…”
Section: Methodsmentioning
confidence: 99%